Hydraulic Modeling and Flood Risk Assessment in the Hola and Bura Basins, Kenya: HEC-RAS-Based Simulation of the March 2024 El-Niño Event - Joseph Tinga , Janga; Edward , Masibayi; Sam , Waweru; Richard , Onchiri (Multidisciplinary Journal of Technical University of Mombasa, 2025)
This study presents a comprehensive hydraulic modeling and flood risk assessment of the Hola and Bura basins in Tana River County, Kenya, using the HEC-RAS 6.7 software. The model simulated the March 2024 El-Niño flood event, a climate-induced extreme rainfall episode, using a two-dimensional (2D) approach to capture complex flow dynamics across floodplains. Coupled with hydrologic inputs from HEC-HMS, the simulation produced detailed flood inundation maps and depth classifications, delineating shallow  m), moderate (0.5–1.5 m), and deep  m) flood zones across a total inundated area of 197.0 km²—representing 39% of the modeled basin. The analysis revealed critical floodplain features such as relict meanders and paleochannels that significantly influenced lateral water spread, emphasizing the importance of preserving natural floodplain connectivity. Validation using Sentinel-1 SAR imagery confirmed strong agreement between observed and simulated flood extents. The present study also assessed the vulnerability of key infrastructure assets, including roads, schools, hospitals, boreholes, and electric transformers. Findings indicate that critical services were either directly inundated or rendered inaccessible due to surrounding flood conditions, with power installations and boreholes particularly at risk due to exposure to deep, high-velocity flows. Based on the spatial hazard classification and exposure overlay, the study proposes targeted design improvements including elevated road embankments, flood-resilient water supply systems, and raised platforms for public utilities. The results demonstrate the value of integrating hydrodynamic modeling with satellite data and infrastructure mapping for informed disaster preparedness, climate adaptation, and land-use planning in flood-prone regions of East Africa.
Keywords: El-Niño, HEC-RAS, Flood Inundation, Critical Infrastructure, 2D Hydraulic Modeling, Climate Risk, Tana River, Kenya